Genetic Diversity and Expanded Phenotypes in Dystonia: Insights From Large‐Scale Exome Sequencing - Mirja Thomsen; Fabian Ott; Sebastian Loens; Gamze Kilic‐Berkmen; Ai Huey Tan; Shen‐Yang Lim; Ebba Lohmann; Kaja M. Schröder; Lea Ipsen; Lena A. Nothacker; Linn Welzel; Alexandra S. Rudnik; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Dystonia is one of the most prevalent movement disorders, characterized by significant clinical and etiological heterogeneity. Despite considerable heritability (~25%), the etiology in most patients remains elusive. Moreover, understanding correlations between clinical manifestations and genetic variants has become increasingly complex. Methods Exome sequencing was conducted on 1924 genetically unsolved, mainly late‐onset isolated dystonia patients, recruited primarily from two dystonia registries (DysTract and the Dystonia Coalition). Rare variants in genes previously linked to dystonia (n = 406) were examined, confirmed via Sanger sequencing, and analyzed for segregation when possible. Results We identified 137 distinct likely pathogenic/pathogenic variants (according to ACMG criteria) across 51 genes in 163/1924 patients, including 153/1895 index patients (diagnostic yield 8.1%). The strongest predictors of a genetic diagnosis were generalized dystonia (28.6% yield) and age at onset (20.4% yield in patients with onset < 30 years). Notably, 56.2% of these variants were novel, with recurrent variants in EIF2AK2, VPS16, KCNMA1, and SLC2A1. Additionally, 321 index patients (16.9%) harbored variants of uncertain significance in 102 genes. The most frequently implicated genes included VPS16, THAP1, GCH1, SGCE, GNAL, and KMT2B. Presumably pathogenic variants in less well‐established dystonia genes were also found, including KCNMA1, KIF1A, and ZMYND11. At least six variants (in ADCY5, GNB1, IR2BPL, KCNN2, KMT2B, and VPS16) occurred de novo, supporting pathogenicity. Interpretation This study provides valuable insights into the genetic landscape of dystonia, underscores the utility of exome sequencing for diagnosis, substantiates several candidate genes, and expands the phenotypic spectrum of some genes to include prominent, sometimes isolated dystonia.